(untitled) (Global Journal of Science Frontier Research, 2014)
Transition behavior from monolayer on the water surface to single particle layer of ternary comb copolymer containing carbazole ring have investigated by surface pressure-area isotherm, atomic force microscopy, X-ray diffraction. This polymer monolayer is able to form the "polymer nanosheet" with amorphous layers and strong interaction between main-chains fabricated by a Langmuir-Blodgett (LB) technique. Further, single particle layer is able to form the multi-particle layered organization of "polymer nanosphere" by LB method. This ternary comb copolymer synthesized by radical copolymerization with hydrogenated and fluorinated long-chain vinyl compounds. Poly(N-vinylcarbazole) homopolymer formed single particle layer on the water surface after spreading, immediately. Spontaneous "particulation" behavior is accelerated by incorporation of carbazole units in ternary copolymer films. Monolayer of these copolymers on the water surface formed below 10 mN m-1, and this monolayer transited to single particle layer above 15 mN m-1.